Intestinal inflammation abrogates the tolerogenic properties of MLN CD103+ dendritic cells. - Laffont, S; Siddiqui, K; Powrie, F (2010)
Intestinal CD103(+) DC promote the differentiation of Foxp3(+) Treg from naïve CD4(+) T cells through mechanisms involving TGF-beta and the dietary metabolite, retinoic acid (RA). In this study, we have analysed whether the specialised features of CD103(+) DC are conserved in colitis. Our results show that inflammation dampens the tolerogenic properties of MLN CD103(+) DC, which is associated with lower expression of tgfbeta2 and aldh1a2. Accordingly, CD103(+) DC taken from colitic mice are impaired in their ability to induce Foxp3(+) Treg and instead favour the emergence of IFN-gamma-producing CD4(+) T cells compared with their steady-state counterparts. BrdU-labelling studies and analysis of ontogeny markers show that CD103(+) DC from steady-state and colitic settings retain similar subset composition and developmental pathways. These results indicate that MLN CD103(+) DC are not hard-wired to promote tolerance but can adapt to environmental conditions. The inflammatory properties of MLN CD103(+) DC in colitic mice may reflect defective gut tolerogenic conditioning or altered migratory pathways and raise the possibility that migratory DC populations contribute to the pathogenesis of inflammatory bowel disease.